(untitled) (Journal of Naval Architecture and Marine Engineering, 2009)
A floating system consisting of three pontoons equispaced, rigidly interconnected and taut moored to act as a single unit is analyzed. The theoretical formulation of the problem is based on the assumptions of irrotational fluid flow, an inviscid fluid, and small incident waves. The breakwater is assumed to be long and uniform in the direction parallel to the incident wave crests. The diffracted and the scattered potentials are obtained from the solution of boundary value problem using Green’s identity method. The potentials and hence the free surface oscillations in between the spacing are also determined. The results of parametric study of varying space and drafts of the pontoons have been presented as a function of relative width of breakwater (Ratio of width of the breakwater to the wavelength) .It is evident from the results that the spaces between the pontoons have a definite effect on transmission and reflection characteristics of a floating breakwater system. As the draft of the floating breakwater increases the bandwidth of incident wave frequencies for which Kt (Ratio of transmitted wave height to incident wave height) is less than 0.2, also increases, thus ensuring a wider spectrum of operation. In addition the paper discusses on forces, oscillations in the interspaces and reflection coefficient. Keywords: breakwater, pontoon, taut moored, free surface oscillations. doi: 10.3329/jname.v1i1.2031 Journal of Naval Architecture and Marine Engineering 1(2004) 3-17